2008
DOI: 10.1097/01.aacn.0000310753.39029.b9
|View full text |Cite
|
Sign up to set email alerts
|

The Shortage of Nurses and Nursing Faculty

Abstract: Nurses are needed more than ever to support the healthcare needs of every American. Nurses make up the greatest single component of hospital staff. In 2004, of the almost 3 million nurses in the United States, 83% were employed in nursing, and 58% of those were employed full-time. However, a severe shortage of nurses exists nationwide, putting the safe, effective healthcare of Americans in jeopardy. The concurrent shortage of nursing faculty has significant impact on the potential for admitting and graduating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Such patients typically have diminished mobility overall and a diminished capacity to perform activities of daily living (ADLs). There is also a shortage of healthcare professionals, especially physicians, nurses, and therapists, which will likely exacerbate the logistics of providing quality care to the expanding senior patient population (Kane et al, 2009; Siela, Twibell, & Keller, 2008; Wilson, Lewis, & Murray, 2009). Other factors may broaden the gap between the need for quality care and the availability of human healthcare professionals to provide it.…”
mentioning
confidence: 99%
“…Such patients typically have diminished mobility overall and a diminished capacity to perform activities of daily living (ADLs). There is also a shortage of healthcare professionals, especially physicians, nurses, and therapists, which will likely exacerbate the logistics of providing quality care to the expanding senior patient population (Kane et al, 2009; Siela, Twibell, & Keller, 2008; Wilson, Lewis, & Murray, 2009). Other factors may broaden the gap between the need for quality care and the availability of human healthcare professionals to provide it.…”
mentioning
confidence: 99%
“…During staff shortages, nurses not only do their job but also do the work of others resulting in stress, dissatisfaction, and subsequently staff turnover [ 35 , 36 , 37 ]. Chen SH et al have shown that human resource practitioners’ responsibilities are to identify means of retaining and engaging staff within the system as they are a valuable commodity that is not readily replaced [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors make nurse turnover a critical issue. First, there is a shortage of nurses in the United States (Auerback, Beurhaus, & Staiger, 2007;Siela, Twibell, & Keller, 2008). Second, this shortage is expected to increase as Baby Boomers retire and nursing schools fail to graduate enough nurses to meet even current demands (Atencio, Cohen, & Gorenberg, 2003).…”
Section: Medical Errorsmentioning
confidence: 99%